Pandangan Dunia Kahlil Gibran dalam Novel Sayap-Sayap Patah - Fuad, Akhmad Dzukaul; Dermawan, Taufik (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
The structure of the novel broken wings consists of ten parts that describe the stages of the "I" love journey. My character is a representation of the author, in another novel he calls himself "the Prophet". As if Kahlil Gibran did not want to part with the structure he created. The depiction of the figure I in each stage displays the dialectics of conflict between structures that form the theme of social inequality. The author examines the structure of the text in the novel broken wings as a thematic structure, the structure of the text is interpreted as social themes that shape social classes based on education and religion. The social reality of society in the novel of broken wings gives birth to binary opposition of social class based on education and religion. Social classifications based on education distinguish educated and barbarians, while classifications based on religion distinguish imams and worshipers. The novel of the broken wings positions the author's partisanship on the young man who fails to fight for his love due to the injustice wrapped up in religious dogma.